ROS-mediated thylakoid membrane remodeling and triacylglycerol biosynthesis under nitrogen starvation in the alga Chlorella sorokiniana - Vijayan, Jithesh; Wase, Nishikant; Liu, Kan; Morse, Wyatt; Zhang, Chi; Riekhof, Wayne R. (Frontiers in Plant Science, 2024)
Many microbes accumulate energy storage molecules such as triglycerides (TAG) and starch during nutrient limitation. In eukaryotic green algae grown under nitrogen-limiting conditions, triglyceride accumulation is coupled with chlorosis and growth arrest. In this study, we show that reactive oxygen species (ROS) actively accumulate during nitrogen limitation in the microalga Chlorella sorokiniana. Accumulation of ROS is mediated by the downregulation of genes encoding ROS-quenching enzymes, such as superoxide dismutases, catalase, peroxiredoxin, and glutathione peroxidase-like, and by the upregulation of enzymes involved in generating ROS, such as NADPH oxidase, xanthine oxidase, and amine oxidases. The expression of genes involved in ascorbate and glutathione metabolism is also affected under this condition. ROS accumulation contributes to the degradation of monogalactosyl diacylglycerol (MGDG) and thylakoid membrane remodeling, leading to chlorosis. Quenching ROS under nitrogen limitation reduces the degradation of MGDG and the accumulation of TAG. This work shows that ROS accumulation, membrane remodeling, and TAG accumulation under nitrogen limitation are intricately linked in the microalga C. sorokiniana.